Attitudes and Digital Financial Literacy towards Performance through the Behavior of Small and Medium Enterprises in Palu City - Fattah, Vitayanti; Surayya, Surayya; Husnah, Husnah; Nurdin, Dhayani; Darman, Darman; Nofal, Muhammad (International Journal of Social Science and Business, 2025)
The proliferation of micro, small, and medium enterprises (MSMEs) has emerged as a pivotal catalyst for economic proliferation. Discussions concerning MSMEs encompass a wide scope, as they pertain to the economic well-being of numerous small communities. The present study aspires to ascertain the impact of attitudes and digital financial literacy on performance, as evidenced by the actions of MSMEs in Palu City. This research was conducted employing a survey method, targeting MSMEs operating within the food and beverage sector in Palu City. This study utilizes a quantitative approach, collecting data through the distribution of questionnaires. The population and sample consist of 92 MSMEs in Palu City. The hypotheses were tested using Smart-PLS analysis. The results indicate that financial attitude and digital financial literacy do not significantly influence the performance of MSMEs in Palu City. However, financial management behavior moderates the influence of financial attitude and digital financial literacy on the performance of MSMEs in Palu City.